The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/403345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Silk assembly integrates cells into a 3D fibrillar network that promotes cell spreading and proliferation

Abstract: Tissues are built of cells integrated in an extracellular matrix (ECM) which provides a threedimensional (3D) fibrillar network with specific sites for cell anchorage. By genetic engineering, motifs from the ECM can be functionally fused to recombinant silk proteins. Such a silk protein, FN-silk, which harbours a motif from fibronectin, has the ability to selfassemble into fibrillar networks under physiological-like conditions. Herein we describe a method by which mammalian cells are added to the silk solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A similar proliferation profile has been seen in other studies wherein spider silk, either recombinant or natural, has been used as a cell culture substrate. [ 34, 35 ] However, not only did the cells survive the cyclic extension and compression process, but they also grew in numbers and maintained metabolically active once integrated into the fibers. Fluorescence images taken on samples stained for actin filaments indicated that the cells were well integrated and stretched out along the direction of the silk fiber (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…A similar proliferation profile has been seen in other studies wherein spider silk, either recombinant or natural, has been used as a cell culture substrate. [ 34, 35 ] However, not only did the cells survive the cyclic extension and compression process, but they also grew in numbers and maintained metabolically active once integrated into the fibers. Fluorescence images taken on samples stained for actin filaments indicated that the cells were well integrated and stretched out along the direction of the silk fiber (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…To address this problem, cells could be encapsulated into fibers during the fiber formation process as recently described. [31] However this procedure may not be applicable to all cell types owing to the shear force required to generate fibers, which could influence differentiation.…”
mentioning
confidence: 99%